Motivasi, Komunikasi, dan Kepuasan Kerja Terhadap Kinerja Tenaga Kependidikan Pada Fakultas Insititut Pertanian Bogor - Nooryani, Sri; Tanjung, Hendri; MA, Ibdalsyah (Jurnal Manajemen, 2016)
The path analysis shows that motivation has significantly direct and indirect effects to communication. Motivation does not have significant effects to performance but have indirect effects through job satisfaction. This is because motivation has significant direct effects to job satisfaction. Communication has direct and indirect effects to performance. The indirect effect is through job satisfaction. Job satisfaction has significant direct effects to performance. The T-test results show that the effects of independent variables (motivation and communication) have significant positive effects to job satisfaction with p-value of 0.00. This value is less than alpha value (5%). Coefficient determination (R2) is of 0.741. This means that motivation and communication can explain the diversity of job satisfaction as high as 74.1% and the rest, which is of 25.9%, explains by other factors that are not used in this research. Independent variables (motivation, communication and job satisfaction) have significant positive effects to performance with p-value of 0.00. The coefficient determination (R2) is of 0.574. This means that motivation, communication, and job satisfaction can explain performance as high as 57.4% and the rest, which is of 42.6%, explains by other factors.